2021
DOI: 10.1186/s12879-021-06936-5
|View full text |Cite
|
Sign up to set email alerts
|

Changing socio-economic and ethnic disparities in influenza/A/H1N1 infection early in the 2009 UK epidemic: a descriptive analysis

Abstract: Background Higher incidence of and risk of hospitalisation and death from Influenza A(H1N1)pdm09 during the 2009 pandemic was reported in ethnic minority groups in many high-income settings including in the United Kingdom (UK). Many of these studies rely on geographical and temporal aggregation of cases and can be difficult to interpret due to the spatial and temporal factors in outbreak spread. Further, it can be challenging to distinguish between disparities in health outcomes caused by varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Among them, Jinfeng County experienced the fastest growth. Mamelund 62 and Munday 63 indicated that socioeconomic conditions influence influenza incidence. According to Yinchuan Statistical Yearbook 64 , Jinfeng District has better socioeconomic conditions compared to other counties.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Jinfeng County experienced the fastest growth. Mamelund 62 and Munday 63 indicated that socioeconomic conditions influence influenza incidence. According to Yinchuan Statistical Yearbook 64 , Jinfeng District has better socioeconomic conditions compared to other counties.…”
Section: Discussionmentioning
confidence: 99%